ECONOMIC EFFICIENCY OF SOYBEAN FARMING (CASE STUDY IN MLORAH VILLAGE REJOSO DISTRICT NGANJUK REGENCY) - Rini Dwiastuti; Indah Mustiko Ningsih (Socio-Economics/Agribusiness Department, 2016)
Since 1992, domestic soybean production was unable to fulfill national consumption, which led to the import decision by government. Domestic farmers have not been interested in cultivating soybean due to its relatively expensive production costs; despite its output price also has less competitiveness to the imported soybean. One strategy to reduce the dependence of imported soybean is by improving the efficiency of soybean farming . Efficiency of soybean production in this research represents the farmers’ ability in having minimum cost to produce certain level of soybean production. This study aims to analyze factors that affect production costs and to estimate the economic efficiency score. Cobb Douglas Stochastic Frontier Cost Function; then, the best models is chosen using Akaike Information Criterion (AIC) and Schwarz Information Criterion (SIC). While, the second objective used actual production cost ratio and minimum production cost ratio. The research finding showed that land lease, fertilizer price, pesticide price, price of drilled wells irrigation, and the amount of output had positive effect to the production costs. Meanwhile, seed price and labor wage had negative effect. In conclusion, farmers still could not achieve economic efficiency, thus, there is a chance to save production cost in order to achieve full economic efficiency.